3D imaging and analysis of skeletal muscle arterial network structure in response to exercise training in normal and overweight mice - Oksaranta, Emilia (2024)
Regular physical activity produces beneficial effects on health in obesity, especially for the vascular system. Three-dimensional imaging (3D) using tissue clearing techniques aids in studying complex structures like vasculature. However, only one preliminary study has examined the 3D skeletal muscle vasculature using similar technique. Since this method has not been extensively studied before, this thesis aimed to develop the method for whole mouse muscles and to investigate the effects of exercise on skeletal muscle arterial network using 3D imaging in normal and overweight mice. Adult C57BL/6J male mice (n=40) were divided into four groups: lean sedentary, lean exercise, obese sedentary and obese exercise. Obesity, hyperglycemia and insulin resistance were induced using a Western diet for 18 weeks. The exercise groups had free access to running wheels for the last 9 weeks within their cages. The entire intervention lasted 18 weeks. Tibialis anterior muscles of mice (n=12, 3/group) were stained with SMA-Cy3 antibody to visualize the arterial network and cleared for 3D vascular structure analysis utilizing light sheet microscopy and Imaris software. Other methods utilized in this study included body composition analysis, glucose tolerance test and maximal running capacity test. Body weight and fat percentage were significantly increased in the obese mice. However, glucose tolerance was impaired only in the obese sedentary group (p<0.0001), demonstrating the metabolic health benefit of exercise in the obese mice. The development of the 3D imaging protocol was successful and visual analysis with Imaris enabled the exploration of the 3D arterial structure. The 3D quantitative analyses revealed no statistically significant differences in arterial characteristics such as area, volume, total length, branch length, diameter, branch level and depth between the groups. 3D visualization of muscles using whole mount staining and iDISCO tissue clearing protocol proved effective in analyzing skeletal muscle arterial vasculature. With this rather small sample size, the results indicate that the arterial network was not affected by exercise and obesity. Further studies using a larger sample size needs to be conducted to evaluate these effects in more detail.